Kepuasan serta harapan mengenai hubungan antara ibubapa dan anak: berdasarkan kawalan fuzzy logic - Mohamad Nasir Saludin,; Rika Fatimah P.L.,; Tan, Yin Chi (2008)
A closer relationship between parent and child will give a positive influence to the development of the state. The present study assessed whether there is a significant differences among satisfaction and expectation of parent-child relationship from the perspective of parents and adolescents. Total of 145 respondents include mothers, fathers and adolescents who aged between 11 years old to 21 years old had been interviewed and completed a set of questionnaire. Fuzzy Logic Controller (FLC) has been used in the present study because of it is more flexible and easy to use in complicated problems compare with other mathematics methods. Processing of collected data has been used program SPSS 11.0 for windows and Matlab 6.5 for windows. Results showed satisfaction of adolescent is higher than parent’s satisfaction on parent-child relationship. Besides that, results also showed that satisfaction in Malays group is higher than Chineses and Indians which have same level of satisfaction. In adolescents’ group, results showed boys have lower level of satisfaction and expectation on parent-child relationship compared with girls. In general, the quality of parent-child relationship has not satisfied both generations, parents and sons. More effort is needed to improve the quality of parent-child relationship to get more favorable relationship